Juno (Journal of Parents and Teachers, 2014)
Teaching card based on the film Juno, directed by Jason Reitman about teenage pregnancy. It suggests activities to do before watching the film, question about specific scenes and reflection activities about teenage pregnancy, unwanted pregnancies, talking about sexuality in the family, contraceptives and abortion
Keywords: cinema and education; cinema and transversal; social issues; teenage pregnancies; abortion.